Hall Current and Joule Heating Effects on Flow of Couple Stress Fluid with Entropy Generation - Opanuga, A. A.; Okagbue, H. I.; Bishop, S. A.; Agboola, O. O. (Engineering, Technology & Applied Science Research, 2018)
In this work, an analytical study of the effects of Hall current and Joule heating on the entropy generation rate of couple stress fluid is performed. It is assumed that the applied pressure gradient induces fluid motion. At constant velocity, hot fluid is injected at the lower wall and sucked off at the upper wall. The obtained equations governing the flow are transformed to dimensionless form and the resulting nonlinear coupled boundary value problems for velocity and temperature profiles are solved by Adomian decomposition method. Analytical expressions for fluid velocity and temperature are used to obtain the entropy generation and the irreversibility ratio. The effects of Hall current, Joule heating, suction/injection and magnetic field parameters are presented and discussed through graphs. It is found that Hall current enhances both primary and secondary velocities and entropy generation. It is also interesting that Joule heating raises fluid temperature and encourages entropy production. On the other hand Hartman number inhibited fluid motion while increase in suction/injection parameter resulted into a shift in flow symmetry.